Identification of Escherichia coli and Trueperella pyogenes isolated from the uterus of dairy cows using routine bacteriological testing and Fourier transform infrared spectroscopy. Issue 1 (December 2016) - Jaureguiberry, María; Madoz, Laura; Giuliodori, Mauricio; Wagener, Karen; Prunner, Isabella; Grunert, Tom; Ehling-Schulz, Monika; Drillich, Marc; Sota, Rodolfo
Abstract Background Uterine disorders are common postpartum diseases in dairy cows. In practice, uterine treatment is often based on systemic or locally applied antimicrobials with no previous identification of pathogens. Accurate on-farm diagnostics are not available, and routine testing is time-consuming and cost intensive. An accurate method that could simplify the identification of uterine pathogenic bacteria and improve pathogen-specific treatments could be an important advance to practitioners. The objective of the present study was to evaluate whether a database built with uterine bacteria from European dairy cows could be used to identify bacteria from Argentinean cows by Fourier transformed infrared (FTIR) spectroscopy. Uterine samples from 64 multiparous dairy cows with different types of vaginal discharge (VD) were collected between 5 and 60 days postpartum, analyzed by routine bacteriological testing methods and then re-evaluated by FTIR spectroscopy (n = 27). Results FTIR spectroscopy identifiedEscherichia coli in 12 out of 14 samples andTrueperella pyogenes in 8 out of 10 samples. The agreement between the two methods was good with a Kappa coefficient of 0.73. In addition, the likelihood for bacterial growth of common uterine pathogens such asE. coli andT. pyogenes tended to increase with VD score. The odds for a positive result toE. coli orT. pyogenes was 1.88 times higher in cows with fetid VD than in herdmates with clear normal VD. Conclusions We conclude that the presence ofE. coli andT. pyogenes in uterine samples from Argentinean dairy cows can be detected with FTIR with the use of a database built with uterine bacteria from European dairy cows. Future studies are needed to determine if FTIR can be used as an alternative to routine bacteriological testing methods.